Prevalence and Factors Associated With Suicidal Ideation Among Children and Adolescents Attending a Pediatric HIV Clinic in Uganda - Namuli, Justine Diana; Nalugya, Joyce Sserunjogi; Bangirana, Paul; Nakimuli-Mpungu, Etheldreda (Frontiers in Sociology, 2021)
Background: Suicidal behavior and HIV/AIDS are major public health challenges especially in low- and middle-income countries. As suicide in adults is perturbing for those closest to them, this sentiment is much more intense and generalized in the case of a child or adolescent. Knowledge of factors associated with suicidal ideation in HIV infected children and adolescents may inform suicide prevention strategies needed to improve their quality of life. This study aimed to assess the prevalence and factors associated with suicidal ideation among HIV infected children & adolescents attending a pediatric HIV clinic in Uganda. Methods: We analyzed data from a sample of 271 children and adolescents aged 6 to 18years living with HIV/AIDS attending a pediatric HIV clinic. Child characteristics and clinical variables were assessed using a socio-demographic questionnaire and medical records respectively. Suicidal ideation and depression were assessed using the Child Depression Inventory. The types of behavioral problems and the Parent –child relationship were assessed using Child Behavioral Check List (6-18years) and the Parent Child Relationship Scale respectively. Child exposure to different stressful life events was assessed with a series of standardized Questions. Logistic regression models were used to explore factors independently associated with suicidal ideation. Results: The prevalence of suicidal ideation was 17%. In the multivariate analysis; Child exposure to family or friend’s death (prevalence rate ratio (PRR = 2.02; 95% CI, 1.01- 4.03), p=0.046) HIV wasting syndrome (PRR=0.39 ;95% CI, 0.21-0.75, p=0.04), Depression (PRR=1.08 ;95% CI, 1.03- 1.12, p=0.001), Anxiety symptoms (PRR=1.10; 95% CI, 1.01-1.20, p=0.024) and Rule breaking behavior (PRR=1.06; 95% CI, 0.99-1.13, p=0.051) were independently associated with suicidal ideations. Conclusion: The prevalence of suicidal ideation among children and adolescents living with HIV/AIDS is substantial. Children and adolescents with exposure to family or friend’s death, those with higher depression scores, Anxiety symptoms and rule breaking behavior scores are more likely to report suicidal ideation. Those with HIV wasting syndrome were less likely to report suicidal ideation. There is urgent need for HIV care providers to screen for suicide and link to mental health services.